Upaya Pengembangan Agribisnis Padi (Oryza Sativa L.) di Kabupaten Indramayu - Wiwik Ambarsari; Vitus Dwi Yunianto Budi Ismadi; Agus Setiadi (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2015)
This research aims to formulate priority of the alternative strategy of the development rice agribusiness and the alternative strategy priority that can be applied to the development of rice agribusiness in Indramayu Regency. This research was done through a survey approach, using descriptive and qualitative analysis. The sampling was done by multistage purposive sampling to 120 rice farmers, and purposive sampling of 15 key persons, namely experts, policy experts, practitioners, businesses, experienced farmers and related agencies. The analysis method used was the Analytical Hierarchy Process (AHP) method with Expert Choice 9.0 Program. The research was conducted from February to August 2014 in Sliyeg, Lelea, and Gabuswetan Districts, Indramayu Regency. The results of this research were the five alternative priorities as the formula of the development strategy of rice agribusiness in Indramayu Regency were the consistency of local government of rice farming development, assurance and protection of the rice price through the modern village barns, the enhancement of agricultural extension workers quality and quantity, development of modern village barns infrastructures, and capital assistance from the Local Owned Enterprises. The key priority alternative strategy of the development rice agribusiness in Indramayu Regency was the consistency of local goverment of rice farming development.